Interlimb and intralimb coordination of rectus femoris and biceps femoris muscles at different running speeds - Kakehata, G.; Goto, Y.; Yokoyama, H.; Iso, S.; Kanosue, K. (Medicine & Science in Sports & Exercise, 2023)
Purpose The purpose of this study was to investigate the relationship between spatiotemporal variables and the muscle activity of the rectus femoris (RF) and biceps femoris (BF) in both legs at various running speeds.